THE EFFECT OF WORK ENVIRONMENT AND MOTIVATION ON EMPLOYEE JOB SATISFACTION IN THE TRANSPORTATION SERVICE KAMPAR REGENCY - Roby Harvino Putra; Zulher Zulher; Azhari Azhari (STIE Bangkinang Publishing, 2023)
This reserch aims to determine the effect of work environment and motivation on job satisfaction of employees at the Department of Transportation, Kampar Regency. The data analysis used in this study is multiple linear regression. The number of respondents in this study to be used as a sample is 37 employees. Hypothesis testing conducted in this study is the F test and t test. Based on the research results, it can be concluded that the work environment and motivation simultaneously have an influence on employee job satisfaction. Based on the partial test results, the work environment has a greater influence on employee job satisfaction because the significant value is smaller than the alpha level of 0.5.